Bilateral cavernous sinus thrombosis by Zygomycetes and Enterococcus - Matos, Ricardo (2019)
We present a case of acute rhinosinusitis complicated with bilateral thrombosis of the cavernous sinus in the adult, aim to alert to its clinical presentation and need for a high index of suspicion. We describe a 53-year-old man presenting with cough and rhinorrhea, with 15 days of evolution, followed by holocranial pulsatile headache, refractory to analgesia, as well as a paresis of the left abducens nerve. After contrastenhanced computed tomography of the cranio-encephalic structures and paranasal sinuses, complete opacification of every right paranasal sinus, associated with erosion of the cribriform plate, bilateral solution of continuity in the para-sphenoidal bone region, and filling defects within the cavernous sinuses were observed, suggesting bilateral cavernous sinuses thrombosis. After endoscopic sinus surgery and directed antibiotic treatment, a good clinical, analytical and imaging evolution were observed, and no neurological sequelae were present.